E-Learning In Pilot Universities Of Modern Distance Education Project In China - Chang, Ying Li (2005)
This paper starts with a case study of China Central Radio & Television University, one of pilot universities in modern distance education project. The case study is intended to provide a descriptive analysis of Web-based educational practices at 68 universities, by focusing on the current state of Web-based education in China and its discernible trends for the future.